Correlates of Work‐Related Disability Among Injured Garment Workers in Bangladesh: A Cross‐Sectional Investigation - Md. Golam Kibria; Mohammad Delwer Hossain Hawlader; Mohammad Hayatun Nabi; S. M. Ali Hasnain Fatme; Shakil Ahmed; Mohammad Monjurul Habib; Sheikh M. Alif; Ahmed Hossain (Health Science Reports, 2026)
ABSTRACT Background and Aims The ready‐made garment (RMG) industry in Bangladesh is crucial for its economy, employing millions of workers. Despite its economic significance, this industry is characterised by unsafe working conditions, resulting in a substantial burden of work‐related injuries. Many injured workers return to their jobs, often experiencing long‐term or permanent disabilities. This study aimed to identify the correlates of work‐related disability among injured garment workers in Bangladesh. Methods A cross‐sectional study was conducted among 730 garment workers who had returned to work (RTW) following workplace injuries. Respondents were recruited from 120 conveniently selected RMG factories in Bangladesh. Work‐related disability was assessed using the Washington Group Short Set on Functioning (WG‐SS) questions. Multivariable logistic regression was performed to identify the factors associated with work‐related disability. Results The prevalence of work‐related disability among injured workers was 13%, with the majority (58.9%) experiencing mobility disability. Male workers (adjusted odds ratio, aOR: 2.0; 95% confidence interval, CI: 1.24 to 3.18), those aged < 30 years (aOR: 2.9; 95% CI: 1.06 to 8.18), and workers from the cutting section (aOR: 2.2, 95% CI: 1.42 to 3.32) had higher odds of work‐related disability. Injury‐related factors associated with a higher likelihood of work‐related disability included bone fractures (aOR: 3.7; 95% CI: 1.81 to 7.53), burn injuries (aOR: 2.4; 95% CI: 1.38 to 4.18), same‐level slips or trips (aOR: 3.8; 95% CI: 2.99 to 4.72), and fire accidents (aOR: 8.2; 95% CI: 1.44 to 46.11). Conclusions This study identified sociodemographic, occupational, and injury‐specific correlates of work‐related disability among injured RMG workers in Bangladesh. These findings highlight the need for interventions to prevent work‐related disability and support injured workers. They also provide evidence to inform occupational health policies and future research.